Microstructure and Mechanical Properties of Modified 316L Stainless Steel Alloy for Biomedical Applications Using Powder Metallurgy - Ali, S. (MDPI, 2022)
AISI 316L stainless steel (SS) is one of the extensively used biomaterials to produce implants and medical devices. It provides a low-cost solution with ample mechanical properties, corrosion resistance, and biocompatibility compared to its counterpart materials. However, the implants made of this material are subjected to a short life span in human physiological conditions leading to the leaching of metal ions, thus limiting its use as a biomaterial. In this research, the addition of boron, titanium, and niobium with varying concentrations in the SS matrix has been explored. This paper explores the impact of material composition on modified SS alloyâs physical and mechanical properties. The studyâs outcomes specify that the microhardness increases for all the alloy compositions, with a maximum increase of 64.68 for the 2 wt. niobium added SS alloy. On the other hand, the tensile strength decreased to 297.40 MPa for the alloy containing 0.25 wt. boron and 2 wt. titanium additions compared to a tensile strength of 572.50 MPa for pure SS. The compression strength increased from 776 MPa for pure SS to 1408 MPa for the alloy containing niobium and titanium additions in equal concentrations. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.